Electrocardiogram (ECG) Pattern of Left Anterior Descending Coronary Artery Occlusion in Acute Anterior Myocardial Infarction Cases - Ishaq, Zeeshan; Nadeem, Asif; Ahmed, Nisar; Ahmed, Iftikhar; Mumtaz, Zahid; Azad, Naseem; Ullah , Fasih; Ghafoor, Atif (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess blockage site in left anterior descending coronary artery by means of Electrocardiogram (ECG).Study Design: Prospective longitudinal study.Place and Duration of Study: Armed forces Institute of Cardiology & National Institute of Heart Diseases, Pakistan from Aug to Feb, 2024.Methodology: This study was conducted on 101 patients with acute anterior wall myocardial infarction (AWMI). Included patients had chest pain in last 12 hours. ECG was done in all patients upon presentation. Localization of occlusion site in LAD territory was identified using pre-specified algorithm. Afterwards, each patient underwent coronary angiography to make sure the findings of ECG for occlusion site in LAD territory. Sensitivity, specificity, positive and negative predictive value and accuracy for ECG patterns were also calculated by taking angiographic findings as gold standard for occlusion site detection.Results: A total of one hundred and one study participants were comprised of 85(84.2%) male and 16(15.8%) female patients and mean age was 61.87±10.39 years.  Among patients with anterior wall myocardial infarction (AWMI), 28 (27.7%) showed blockage in LAD before origin of both 1st septal(S1) and 1st diagonal(D1) branch. For occlusions before origin of S1 and after D1, after S1 and before D1, and after both S1 and D1, the numbers were 7(6.9%), 8 (7.9%), and 58(57.4%), respectively.Conclusion: ECG is not only useful in guiding the timely administration of reperfusion therapy but also in offering insights into the severity and site of blockage in individuals diagnosed with AWMI before encountering angiography.